How the older market is evolving internationally - Stroud, Dick; Walker, Gill; Nyren, Chuck; in’t Veld, Arjan (Henry Stewart Talks, 2009)
The status of UK 50 plus marketing, The Australian perspective, Advertising and marketing to baby boomers in the USA, Marketing and advertising to the older consumer in the Netherlands